International Police Records and the Control of Juveniles. Politics and Policing in a Suburban Town - Meehan, Albert J. (The British journal of criminology, 1993)
This paper examines the consequences of external (i.e., community) and internal (i.e., administrative) pressure on the police to discourage the arrest and formal processing of a community's Juveniles. The department's response resulted in a shift to surveillance and the development of internal recordkeeping as the primary form of control. Thus, the police were able to satisfy the community's demand and their own organizational needs for information regarding the nature and extent of juvenile deviance at the same time. However, increased reliance on surveillance bypasses not only the stigma of the formal process, but also its guarantees, and thereby ironically increases police control over juveniles. The results of informal recordkeeping practices also have implications for understanding official crime statistics. That is, departments are able to manage' their crime rates so that towns with apparently equal levels of juvenile deviance have very different official rates' of juvenile crime